2019
DOI: 10.1007/jhep03(2019)071
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology with a very light Lμ − Lτ gauge boson

Abstract: In this paper, we explore in detail the cosmological implications of an abelian L µ − L τ gauge extension of the Standard Model featuring a light and weakly coupled Z . Such a scenario is motivated by the longstanding ∼ 4σ discrepancy between the measured and predicted values of the muon's anomalous magnetic moment, (g − 2) µ , as well as the tension between late and early time determinations of the Hubble constant. If sufficiently light, the Z population will decay to neutrinos, increasing the overall energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
281
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 244 publications
(288 citation statements)
references
References 59 publications
7
281
0
Order By: Relevance
“…Planck CMB observations are more stringent than BBN and set T dec The bound on the neutrino decoupling temperature is generic and can be directly mapped into a constraint on the mass and couplings of various BSM species interacting both with neutrinos and electrons. The phenomenology of such type of scenarios has been studied in detail in the context of a very light U (1) µ−τ gauge boson [83], but from Equation (18)…”
Section: V2 Constraintsmentioning
confidence: 99%
“…Planck CMB observations are more stringent than BBN and set T dec The bound on the neutrino decoupling temperature is generic and can be directly mapped into a constraint on the mass and couplings of various BSM species interacting both with neutrinos and electrons. The phenomenology of such type of scenarios has been studied in detail in the context of a very light U (1) µ−τ gauge boson [83], but from Equation (18)…”
Section: V2 Constraintsmentioning
confidence: 99%
“…This loop-induced kinetic mixing, as defined in Eq. (4.1), is related to the L α − L β gauge coupling g αβ as [63,83,89]…”
Section: Section 5: Leptophilic Gauge Bosonsmentioning
confidence: 99%
“…[5,6]), that the U(1) L µ −L τ gauge boson, Z µτ , with an MeV scale mass can settle the long-standing discrepancy of muon anomalous magnetic moment (g µ − 2) [7][8][9][10][11][12] without conflicting other experimental constraints. Then, this result motivated many authors to study low scale U(1) L µ −L τ extension of the SM in various contexts: for instance, it was found that an MeV scale Z µτ can relax the tension between the late time and the early time determination of the Hubble constant [13], implications for the dark matter problem were studied in Refs. [14][15][16][17], and the detectability of such a light Z µτ was discussed in Refs.…”
Section: Introductionmentioning
confidence: 93%